Estudo da ação do inseticida Tiametoxam na sobrevivência e no comportamento de operárias de Apis mellifera L., 1758 (Hymenoptera: Apidae) em diferentes idades - Nominato, Fellipe Chaves [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The bee Apis mellifera has a great importance because it is the most economically valuable pollinator for crops worldwide, ensuring cross-pollination and increasing fruit yield. Moreover, agriculture increasingly develops chemicals to control weeds, fungi and insect pests to ensure productivity. Insecticides are used on a large scale in the state of São Paulo, in cultures of citrus for control of greening. Applications are usually made by aircraft and as a result of the effect derives a significant mortality is observed in apiaries near the plantations. Honey bees can get in contact with such chemical agent through their activities of water harvesting, plant resins, pollen and nectar. Intoxication resulting from this exposure can be lethal, which is easily detectable, or cause effects on the physiology and behavior of the insect. These, in turn are hardly detectable, such as paralysis, disorientation, behavioral changes, but can compromise the entire social structure of the colony, therefore aimed to study the effects of the insecticide Thiamethoxam behavior of honeybees A. mellifera. Newly emerged individuals and with 10 days of age were tested. Applications of 1 μL de Thiamethoxam, diluted in acetone, were made on the dorsal thorax with a microapplicator. Preliminarily, it was observed LD50 twenty four hours after topical treatment of Thiamethoxam. It was found that the LD50 for newly emerged honeybees is 8 ng/bee and for honeybees with 10 days of age is 18 ng/bee. The behaviors were analyzed 1 hour after application of insecticide at doses corresponding to LD50/100, LD50/50, LD50/10 and LD50, besides the control group. In the test reflex proboscis extension, there was impairment of behavior at doses of 8 and 18 ng/bee workers in newly emerged workers and 10 days of age, respectively. And in locomotor behavior was no change only at a dose of 18 ng/bee workers at 10 days of age... (Complete abstract click electronic access below)

A abelha Apis mellifera tem sua grande importância por ser o polinizador economicamente mais valioso para as culturas em todo o mundo, garantindo a polinização cruzada e aumentando a produtividade de frutos. Por outro lado, a agricultura cada vez mais desenvolve produtos químicos a fim de controlar plantas daninhas, fungos e inseto-praga para garantir a produtividade. Os inseticidas são utilizados em grande escala no interior do estado de São Paulo, nas culturas de citrus para o controle do greening. As aplicações normalmente são feitas por aviões e como resultado do efeito deriva, uma mortandade expressiva é observada em apiários próximos das plantações. As abelhas melíferas podem entrar em contato com tal agente químico através de suas atividades de coleta de água, resinas vegetais, pólen e néctar. A intoxicação resultante desta exposição pode ser letal, o que é facilmente detectável, ou causar efeitos na fisiologia e no comportamento do inseto. Esses, que por sua vez são dificilmente detectáveis, como paralisia, desorientação ou mudanças comportamentais; porém podem comprometer toda a estrutura social da colônia, por esta razão objetivou-se estudar os efeitos do inseticida Tiametoxam no comportamento de abelhas A. mellifera. Indivíduos recém-emergidos e com 10 dias de idade de A. mellifera foram testados. Aplicações de 1μl de Tiametoxam, diluído em acetona, foram feitas no lado dorsal do tórax com um microaplicador. Preliminarmente, observou-se a DL50 vinte e quatro horas após o tratamento tópico. Verificou-se que a DL50 para abelhas africanizadas recém-emergidas é 8 ng/abelha, e para abelhas africanizadas com 10 dias de idade é 18 ng/abelha. Os comportamentos foram analisados 1 hora após a aplicação do inseticida com doses que correspondem a DL50, DL50/10, DL50/50 e DL50/100, além do grupo controle... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Inseticidas; Abelha; Abelha-africanizada; Abelha - Aspectos fisiológicos; Intoxicação; Reflexos; Capacidade motora